ANALISIS PENGARUH KOMPETENSI GURU SKI BERBASIS TPACK TERHADAP PENINGKATAN HIGHER ORDER THINKING SKILL (HOTS) SISWA MADRASAH IBTIDAIYAH - Dinny Arifatul Hidayah; Fathia Nisa’un Nabil; Munawir (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
Abstract: This study aims to analyze the influence of Islamic Cultural History teacher competencies based on TPACK (Technological Pedagogical Content Knowledge) on improving the Higher Order Thinking Skills (HOTS) abilities of Islamic Elementary School (MI) students. This study uses a library research method with data collection techniques in the form of analysis of relevant literature, such as scientific journals, textbooks, and curriculum policies related to is teaching. The data analysis techniques used are content analysis and critical synthesis of various previous research findings. The results of the study indicate that the integration of technological, pedagogical, and material knowledge (TPACK) by IS teachers is a crucial instrument in transforming textual history learning into more interactive and analytical. TPACK competencies have proven effective in facilitating teachers to design learning tools that are able to stimulate critical thinking and creativity of students in accordance with HOTS standards. These findings conclude that strengthening TPACK-based teacher competencies is a fundamental prerequisite for the successful implementation of HOTS-oriented learning at the Islamic Elementary School level.   Abstrak: Penelitian ini bertujuan untuk menganalisis pengaruh kompetensi guru Sejarah Kebudayaan Islam (SKI) berbasis TPACK (Technological Pedagogical Content Knowledge) terhadap peningkatan kemampuan Higher Order Thinking Skills (HOTS) siswa Madrasah Ibtidaiyah (MI). Penelitian ini menggunakan metode studi kepustakaan (library research) dengan teknik pengumpulan data berupa analisis terhadap literatur yang relevan, seperti jurnal ilmiah, buku teks, dan kebijakan kurikulum terkait pengajaran SKI. Teknik analisis data yang digunakan adalah analisis isi (content analysis) dan sintesis kritis dari berbagai temuan penelitian sebelumnya. Hasil penelitian menunjukkan bahwa integrasi pengetahuan teknologi, pedagogi, dan materi (TPACK) oleh guru SKI merupakan instrumen krusial dalam mentransformasi pembelajaran sejarah yang bersifat tekstual menjadi lebih interaktif dan analitis. Kompetensi TPACK terbukti efektif dalam memfasilitasi guru untuk merancang perangkat pembelajaran yang mampu menstimulasi nalar kritis dan kreativitas siswa sesuai dengan standar HOTS. Temuan ini menyimpulkan bahwa penguatan kompetensi guru berbasis TPACK menjadi prasyarat fundamental bagi keberhasilan implementasi pembelajaran berorientasi HOTS di jenjang Madrasah Ibtidaiyah.